The Batujaya Temple Complex As Vihara In The 7th Century - Indradjaja, Agustijanto (Kodepena Indonesia, 2024)
The Batujaya Temple in Karawang Regency, West Java is the largest Buddhist temple complex in Java. At least now it is known more than 40 remaining building structures in an area of ​​2 x 2.5 km. The findings of the remains of the building structure are not only in the form of a stupa but also the remains of other building structures that reflect the complexity of activities at this site. This paper will identify a number of other building components found in Batujaya Temple. Data was collected through surveys and excavations. The analysis was carried out by making a number of comparisons with the findings of other sites. The research succeeded in identifying a number of building components that were needed for a center of worship and teaching (monastery). Based on the identification of a number of archaeological findings, it appears that the Batujaya temple complex is not only used as a worship center but also as a center for Buddhist teachings in West Java. Like the two centers of Buddhist studies in the archipelago, namely Sriwijaya and Ho-ling (Java) in the 7thcentury AD.